2007
DOI: 10.4102/ac.v7i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Employment of people with disabilities: Implications for HR management practices

Abstract: Purpose: The purpose of this paper is to, firstly, present the findings of an empirical study in which the human resource management practices associated with the employment of people with disabilities were investigated. The human resource management challenges related to employment of people with disabilities were also identified in the empirical study and are presented in this paper. A further purpose of this paper is to propose a number of recommendations focused on human resource management practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Guimaraes, Martins and Barkokebas Junior (2012) found that a lack of professional training, architectonic barriers and discrimination based on functional potential hinder the inclusion of people with disabilities in the labour market. According to Gida and Ortlepp (2007), ignorance, fear and stereotypes are the main reasons for a low representation of people with disabilities in the workplace. Gida and Ortlepp (2007) noted that organisations do not have a strategy or policy document for the employment of people with disabilities.…”
Section: Promotion Of Equality and Prevention Of Unfair Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Guimaraes, Martins and Barkokebas Junior (2012) found that a lack of professional training, architectonic barriers and discrimination based on functional potential hinder the inclusion of people with disabilities in the labour market. According to Gida and Ortlepp (2007), ignorance, fear and stereotypes are the main reasons for a low representation of people with disabilities in the workplace. Gida and Ortlepp (2007) noted that organisations do not have a strategy or policy document for the employment of people with disabilities.…”
Section: Promotion Of Equality and Prevention Of Unfair Discriminationmentioning
confidence: 99%
“…According to Gida and Ortlepp (2007), ignorance, fear and stereotypes are the main reasons for a low representation of people with disabilities in the workplace. Gida and Ortlepp (2007) noted that organisations do not have a strategy or policy document for the employment of people with disabilities. The South African Human Rights Commission (2012) advocated that scarce employment opportunities and inadequate marketable skills exacerbate the unemployment of candidates with disabilities.…”
Section: Promotion Of Equality and Prevention Of Unfair Discriminationmentioning
confidence: 99%
“…Since democracy in 1994, governing bodies have developed policies and legislation, which are aligned with international policies, to address issues surrounding fairness and promote equality within society (Maja, Mann, Sing, Steyn, & Naidoo, 2011). Between 1993 and 2000, several important Acts were passed by South African governing bodies that cumulatively impacted on employment and workplace practices (Gida & Ortlepp, 2007). Although the legislation was not disability-specific, it made provisions for persons with disabilities (International Labour Organisation Skills and Employment Department, 2007).…”
Section: South African Policies and Legal Framework On Disability Andmentioning
confidence: 99%
“…Emphasis is placed on altering mindsets and is not sufficiently useful to manage disability in the workplace (van Staden, 2011). Regarding disability, the EEA is considered progressive as it aims to redress employment disadvantages as experienced by designated groups (Gida & Ortlepp, 2007), promote their rights, prohibit discrimination, and obligate employers to provide accommodations based on the needs of individuals with disabilities (Modise et al, 2014). It requires fair treatment in all aspects of employment including recruitment, promotion, training and advancement for all, including people with disabilities (Majola & Dhunpath, 2016).…”
Section: National Disability Strategy (Inds) Of 1997mentioning
confidence: 99%
“…Furthermore, implementation, which involves translating policy into practice (Poon-McBrayer and Wong, 2013) has been uneven. While the employment of people with disabilities has received considerable attention in labor legislation and supporting documents (Gida and Ortlepp, 2007), there is a dearth of empirical research on the development of disability employment policies in both developed and developing countries. It is against this background that this article explores the development of workplace of disability employment policies that are the key to the employment of people with disabilities.…”
Section: Introduction mentioning
confidence: 99%